ANALISIS YURIDIS TERHADAP PELANGGARAN HAK CIPTA ATAS PEMUTARAN MUSIK DI TEMPAT UMUM OLEH PERUSAHAAN MIE GACOAN DI BALI BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 - fredi, Kadek Frediandrika Adnantara (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2025)
The enforcement of copyright on musical works in Indonesia has been expressly regulated in Law Number 28 of 2014 concerning Copyright. One form of infringement that often occurs is the playing of music in public places without permission from the copyright holder. The researcher analyzed copyright infringement committed by the Mie Gacoan company in Bali, which played music in its business area without obtaining a license or permit from the Collective Management Institution (LMK) as the representative of the copyright owner. This research uses a normative juridical approach by examining the provisions of laws and regulations and case studies that occur. The results of the analysis show that these actions include violations of the economic rights of the creator as referred to in Article 9 and Article 113 of the Copyright Law. In addition, companies can be subject to civil sanctions in the form of damages and criminal fines. The researcher emphasized the importance of legal awareness of business actors on the licensing obligation of the use of copyrights and the need to strengthen the supervisory and law enforcement functions by the authorities.